2012
DOI: 10.1074/jbc.m111.328187
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific Protease 4 Mitigates Toll-like/Interleukin-1 Receptor Signaling and Regulates Innate Immune Activation

Abstract: Background:The TRAF6-mediated Toll-like receptor (TLR)/IL-1 receptor (IL-1R) pathway is essential for innate immune responses and immune homeostasis. Results: USP4 deubiquitinates Lys-63-linked polyubiquitination of TRAF6 and thereby prevents the TLR/IL-1R-induced activation of NF-B and AP-1 transcription factors and subsequent proinflammatory responses. Conclusion: USP4 plays an essential role in the negative regulation of the TLR/IL-1R signaling-mediated innate immune response. Significance: USP4 is an attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 40 publications
3
61
0
Order By: Relevance
“…In MEF and Raw264.7 cells, polyubiquitination of TRAF6 was increased after IL-1β or LPS treatment, as reported previously [15]. Importantly, depletion of UBE2O by two independent shRNAs enhanced IL-1β-or LPS-induced polyubiquitination of TRAF6 in these cells ( Figure 4A and 4B).…”
Section: Knockdown Of Ube2o Enhances Traf6 Polyubiquitinationsupporting
confidence: 86%
See 4 more Smart Citations
“…In MEF and Raw264.7 cells, polyubiquitination of TRAF6 was increased after IL-1β or LPS treatment, as reported previously [15]. Importantly, depletion of UBE2O by two independent shRNAs enhanced IL-1β-or LPS-induced polyubiquitination of TRAF6 in these cells ( Figure 4A and 4B).…”
Section: Knockdown Of Ube2o Enhances Traf6 Polyubiquitinationsupporting
confidence: 86%
“…Activated TRAF6 functions as an adaptor protein to activate downstream transcription factors. It has been shown that K63 auto-polyubiquitination of TRAF6 is essential for its activation, and is counteracted by the deubiquitnases A20, CYLD, MCPIP1, USP4 or USP2a [14][15][16][17][18]25]. In our study, we found that UBE2O binds endogenous TRAF6 and inhibits both K48-and K63-polyubiquitination of TRAF6.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations